Prospek Relasi Dewan Perwakilan Daerah Dengan Partai Politik - Bagir Manan; Indra Perwira; Mei Susanto (Fakultas Hukum Universitas Islam Indonesia, 2021)
This article analyzes the relationship between the Regional Representative Council (DPD) and political parties that are often confronted diametrically. The questions presented, what is the historical factor for the formation of the DPD and the comparison of the practices of several countries in relation to regional representative bodies and political parties? What are the prospects for the relationship between the DPD and political parties in the future? This article aims to provide a different perspective on the relationship between the DPD and political parties from the historical, comparative and conception point of regional representation bodies. Through the socio-legal method, it was concluded that, first, historically the formation of the DPD was designed to be filled by individuals, not political parties. However, the practice of some countries shows that regional representative bodies generally cannot be separated from political parties. The lesson is that separating the DPD and political parties